Evaluation of moxifloxacin-hydroxyapatite composite graft in the regeneration of intrabony defects: A clinical, radiographic, and microbiological study - Y V Nagarjuna Reddy; P C Deepika; M P Venkatesh; K G Rajeshwari (Wolters Kluwer Medknow Publications, 2016)
Background: The formation of new connective periodontal attachment is contingent upon the elimination or marked reduction of pathogens at the treated periodontal site. An anti-microbial agent, i.e. moxifloxacin has been incorporated into the bone graft to control infection and facilitate healing during and after periodontal therapy. Materials and Methods: By purposive sampling, 15 patients with at least two contralateral vertical defect sites were selected. The selected sites in each individual were divided randomly into test and control sites according to split-mouth design. Test site received moxifloxacin-hydroxyapatite composite graft and control site received hydroxyapatite-placebo gel composite graft. Probing depth (PD) and Clinical attachment level (CAL) were assessed at baseline, 3, 6, 9, and 12 months. Bone probing depth (BPD) and hard tissue parameters such as amount of defect fill, percentage of defect fill, and changes in alveolar crest were assessed at baseline, 6, and 12 months. Changes in subgingival microflora were also assessed by culturing the subgingival plaque samples at baseline and at 3-month follow-up. The clinical, radiographic, and microbiological data obtained were subjected to statistical analysis using descriptive statistics, paired sample t-test, independent t-test, and contingency test. Results: On intragroup comparison at test and control sites, there was a significant improvement in all clinical and radiographic parameters. However, on intergroup comparison of the same, there was no statistically significant difference between test and control sites at any interval. Although test sites showed slightly higher amount of bone fill, it was not statistically significant. There was a significant reduction in the counts of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis at both sites from baseline to 3 months. In addition, there was a significant reduction at test sites as compared to control sites at 3-month follow-up (P = 0.003 and P = 0.013). Conclusion: The reduction in microbial counts found in test sites at 3-month follow-up could not bring similar significant improvements in the clinical and radiographic parameters though the test sites showed slightly higher bone fill.